Live cell analysis at sea reveals divergent thermal performance between photosynthetic ocean microbial eukaryote populations - McInnes, A.; Laczka, O.; Baker, K.; Larsson, M.; Robinson, Charlotte; Clark, J.; Laiolo, L.; Alvarez, M.; Laverock, B.; Kremer, C.; van Sebille, E.; Doblin, M. (2019)
Experimentation at sea provides insight into which traits of ocean microbes are linked to performance in situ. Here we show distinct patterns in thermal tolerance of microbial phototrophs from adjacent water masses sampled in the south-west Pacific Ocean, determined using a fluorescent marker for reactive oxygen species (ROS). ROS content of pico-eukaryotes was assessed after 1, 5 and 25 h of incubation along a temperature gradient (15.6–32.1 °C). Pico-eukaryotes from the East Australian Current (EAC) had relatively constant ROS and showed greatest mortality after 25 h at 7 °C below ambient, whereas those from the Tasman Sea had elevated ROS in both warm and cool temperature extremes and greatest mortality at temperatures 6–10 °C above ambient, interpreted as the outcome of thermal stress. Tracking of water masses within an oceanographic circulation model showed populations had distinct thermal histories, with EAC pico-eukaryotes experiencing higher average temperatures for at least 1 week prior to sampling. While acclimatization and community assembly could both influence biological responses, this study clearly demonstrates that phenotypic divergence occurs along planktonic drift trajectories.